Effectiveness of non-pharmacological interventions to decrease fatigue in people living with HIV/AIDS: a protocol of systematic review and meta-analysis. Issue 9 (22nd September 2020) - Xiao, Xueling; Reynolds, Nancy R; Saligan, Leorey; Lei, Yunxiao; Wang, Min; Wang, Honghong
Abstract : Introduction: Fatigue is a common symptom among people living with HIV (PLWH). It has a substantial adverse impact on functional status and the ability to conduct activities of daily living. Identifying effective strategies to prevent or reduce fatigue is significant to promote the quality of life of this vulnerable population. The purpose of this review is to synthesise the non-pharmacological evidence and assess the effects of interventions on reducing HIV-related fatigue among PLWH. Methods and analysis: We will comprehensively search literature available up to 30 June 2020, in the following databases: PubMed, Embase, CINAHL, Cochrane Library, Web of Science and PsycINFO. The reference list of selected studies and relevant published reviews will also be screened to retrieve potential articles. Two reviewers will identify the eligible articles, extract data and identify the biases in the selected studies. Any disagreements will be referred to a third reviewer. We will qualitatively synthesise the evidence and pool data with meta-analysis according to the heterogeneity of different studies. Ethics and dissemination: This systematic review will not raise any ethical issues since it is a secondary data collection and analysis. The results will inform effective strategies to reduce fatigue among PLWH. The final report will be published in a peer-reviewed journal and academic conferences. PROSPERO registration number: CRD42020153715.